Implementing Levodopa‐Carbidopa Intestinal Gel for Parkinson Disease: Insights from US Practitioners. Issue 4 (27th June 2018) - Burack, Michelle; Aldred, Jason; Zadikoff, Cindy; Vanagunas, Arvydas; Klos, Kevin; Bilir, Bahri; Fernandez, Hubert H.; Standaert, David G.
Abstract: Background: Levodopa‐carbidopa intestinal gel (LCIG, designated in the United States as carbidopa‐levodopa enteral suspension, CLES) was approved in the United States in 2015 for the treatment of refractory motor fluctuations in individuals with Parkinson disease (PD). Many neurologists in the United States have not had personal experience with implementation and management of the unique delivery system for this treatment. Methods and Findings: This educational review was developed to provide practitioners with an understanding of LCIG use from the clinician's point of view. Practical recommendations for the use of LCIG from the early planning stages through long‐term patient management were compiled from the published literature, regulatory guidance, and clinical experience. Among the topics reviewed were: assembling a multidisciplinary treatment team, identifying treatment candidates, patient/care partner education, procedural considerations, post‐procedural care, LCIG initiation and titration, troubleshooting issues, and ongoing monitoring. For most of these steps, a considerable amount of individualization is possible, which allows clinicians to tailor protocols based on the needs of their teams, the healthcare system, and the patient and care partner. Although clinical practices are heterogeneous, themes of early planning, ongoing education, and a team‐based approach to management are universal. Conclusions: By using established protocols and insights gleaned from experienced practitioners, clinicians who are unfamiliar with LCIG can more feasibly incorporate this treatment option into their armamentarium for treating PD motor fluctuations.